Term breech presentation vaginal births in Tibet: A retrospective analysis of 451 cases - Long, Fang; Yan, Keqing; Guo, Dongxing; Zhaxi, Duoji; Xu, Xiaoguang; Sun, Zhigang; Xiao, Zhen (Frontiers in Medicine, 2023)
Background: In high altitude areas, like Tibet, most fetuses in breech presentation at term are delivered vaginally owing to a variety of reasons, but this has not been published. Objective: This study aimed to provide references and evidence for the delivery of breach presentation term fetuses in high altitude areas, through comparing and analyzing the data of full-term singleton fetuses with breech or cephalic presentation in Naqu People's Hospital, Tibet. Study design: We retrospectively analyzed the clinical data of 451 breech presentation fetuses mentioned above over a period of 5 years (2016–2020). A total of 526 cephalic presentation fetuses’ data within three months (1 June to 1 September 2020) of the same period were collected too. Statistics were compared and assembled on fetal mortality, Apgar scores, and severe neonatal complications for both planned cesarean section (CS) and vaginal delivery. In addition, we also analyzed the types of breech presentation, the second stage of labor, and damage to the maternal perineum during vaginal delivery. Results: Among the 451 cases of breech presentation fetuses, 22 cases (4.9%) elected for CS and 429 cases (95.1%) elected for vaginal delivery. Of the women who chose vaginal trial labor, 17 cases underwent emergency CSs. The perinatal and neonatal mortality rate was 4.2% in the planned vaginal delivery group and the incidence of severe neonatal complications was 11.7% in the transvaginal group, no deaths were detected in the CS group. Among the 526 cephalic control groups with planned vaginal delivery, the perinatal and neonatal mortality was 1.5% (P=0.012), and the incidence of severe neonatal complications was 1.9%. Among vaginal breech deliveries, most of them were complete breech presentation (61.17%). Among the 364 cases, the proportion of intact perinea was 45.1%, and I° lacerations accounted for 40.7%. Conclusion: In the Tibetan Plateau region, vaginal delivery was less safe than cephalic presentation fetuses for full-term breech presentation fetuses delivered in the lithotomy position. However, if dystocia or fetal distress can be identified in time and then encouraged to convert to cesarean, its safety will be greatly improved.